Iridium(III)-Catalyzed Difluoroalkylation–Bicyclization of 1,7-Enynes toward Benzo[a]fluoren-5-ones under Visible-Light Photoredox Conditions - Huang, Min-Hua; Hao, Wen-Juan; Jiang, Bo (Synthesis, 2020)
A new visible-light-induced Ir(III)-catalyzed difluoroalkylation–bicyclization of 1,7-enynes with ethyl 2-bromo-2,2-difluoroacetate (BrCF2CO2Et) is described, furnishing a wide range of difluoromethyl-containing benzo[a]fluoren-5-ones in good to excellent yields. The reaction is operationally simple, proceeds with high efficiency under mild conditions, and shows excellent functional group compatibility.
Keywords: difluoroalkylation; bicyclization; 1,7-enynes; photocatalysis; benzo[a]fluoren-5-ones